A case of McLeod syndrome caused by a nonsense variation c.942G>A in the XK gene: A case report - Ying, Yanling; Yu, Shifang; Zhang, Jingjing; He, Ji; Xu, Xianguo; Hong, Xiaozhen; Zhu, Faming (Frontiers in Genetics, 2023)
McLeod syndrome is a rare XK gene-related progressive, debilitating disease involving multiple systems. Blood group phenotypes in McLeod syndrome patients usually display Kx antigen loss and a decrease in Kell blood group system antigen expression. This paper describes a 41-year-old male Chinese patient with McLeod syndrome. He first attended a hospital in 2015 and developed progressively worsening symptoms 4 years ago. As the disease progressed, the patient exhibited memory loss, unresponsiveness and chorea and displayed elevated creatine kinase levels. However, McLeod syndrome could not be diagnosed by these signs and laboratory results. The patient was readmitted to the hospital in 2020 and was suspected of having McLeod syndrome. Then, serological analysis of the Kell blood group system and genotyping for the XK blood group system were performed, revealing weak expression of the k antigen and negative K antigen. Sequencing of the coding region of the XK gene showed a hemizygous c.942G>A variation in the XK gene, which resulted in a premature stop codon at position 314 (p.Trp314Ter). Therefore, the patient was diagnosed with McLeod syndrome. In conclusion, this paper presents a case of McLeod syndrome caused by a nonsense variation c.942G>A in the XK gene. Analysis of the XK gene and blood group antigens are helpful for the diagnosis of McLeod syndrome and distinguishes it from many other diseases.